Spatial correlations in ground motion intensity measuring from the 2023 Türkiye earthquake - Guoliang Shao; Ruizhi Wen; Hongwei Wang; Yeifei Ren; Baofeng Zhou (Earthquake Research Advances, 2024)
When evaluating an area's seismic risk or resilience, it is necessary to use the spatial correlation to analyze the ground motion parameters of multiple sites together in an earthquake. These two large earthquakes in Türkiye provided the possibility for spatial correlation analysis of ground motion intensity measurements in this area. Based on the strong motion records provided by The Disaster and Emergency Management Authority of Türkiye (AFAD), this study uses the local ground motion prediction equation ​in Türkiye to give spatial correlation analysis of Intensity Measurements. This study gives an exponential model based on a semivariogram and compares it with the correlation model obtained from previous studies.